LINC00892 as a Prognostic Biomarker in Lung Adenocarcinoma: Role in Immune Infiltration and EMT Suppression - Xinyu Luan; Xuxing Peng; Qinghua Hou; Jixian Liu (Journal of Immunology Research)
Lung adenocarcinoma (LUAD) is a prevalent and aggressive form of lung cancer with poor prognosis, largely due to late-stage diagnosis and limited therapeutic options. Recent studies suggest that long noncoding RNAs (lncRNAs) play critical roles in cancer progression and immune modulation, emerging as potential therapeutic targets. In this study, we investigated the expression and functional role of LINC00892 in LUAD using RNA sequencing data from The Cancer Genome Atlas (TCGA) and functional assays in vitro and in vivo. We found that LINC00892 is significantly downregulated in LUAD tissues compared to normal tissues, and lower LINC00892 expression correlates with poorer overall survival (OS), disease-specific survival (DSS), and progression-free interval (PFI), particularly in younger patients and those with early-stage disease. Bioinformatic analyses revealed that LINC00892 expression is positively correlated with immune cell infiltration, including CD4+ and CD8+ T cells, and negatively correlated with tumor-promoting Th2 cells, suggesting its role in shaping the tumor immune microenvironment. In vitro functional assays showed that LINC00892 overexpression inhibits LUAD cell proliferation, migration, and invasion while promoting apoptosis. Mechanistically, LINC00892 upregulation was found to suppress epithelial–mesenchymal transition (EMT) by increasing E-cadherin expression and decreasing levels of N-cadherin, vimentin, and slug. Additionally, in an in vivo mouse xenograft model, LINC00892 overexpression suppressed tumor growth and metastasis, accompanied by enhanced immune cell infiltration such as CD4+ and CD8+ T cells. Collectively, these findings suggest that LINC00892 acts as a tumor suppressor in LUAD by modulating immune infiltration and EMT, highlighting its potential as a prognostic biomarker and therapeutic target.